Policing, Race, and Politics in Chicago - Pihos, Peter Constantine (2015)
Policing, Race, and Politics in Chicago asks how local political institutions structured the relationship between race and policing in Chicago. It follows Renault Robinson, the Afro-American Patrolmen’s League, and their allies, as they challenged both a political order in which black politicians and voters played critical roles and a Police Department that had the most black officers of any in the United States by the early 1960s. Their activism impelled recognition that Richard J. Daley’s Democratic Party and city government simultaneously incorporated and subordinated black urbanites. Daley’s political monopoly forced the League to seek leverage outside of local electoral politics, through tactics that included citizen monitoring, legal challenges, alliances with state and federal political actors and institutions, and, ultimately, political revolt. The rise of “law and order” among police officers in the mid-1960s was only half of a more complicated story in Chicago. League members challenged their colleagues and the blue wall of silence by working with black communities and police reform activists. They participated in the creation of a network of organizations, the institutionalization of which increased the capacity of citizens to monitor police behavior. They also engaged the federal government, whose transfer of federal funds to state and local criminal justice agencies was more than a catalyst for punitive policies. The League’s efforts to use Title VI to compel civil rights compliance produced more robust federal civil rights enforcement and this, in turn, transformed local personnel practices. Finally, their struggle over policing provided a wedge issue for black politicians to break from the regular Democrats. Robinson and the League facilitated this transition from politics to protest, playing key roles in forging an insurgent movement to defeat the machine. Despite their success in Harold Washington’s epic 1983 mayoral victory, their experience tracked growing intra-racial stratification. Even as the Mayor sought to deliver greater public safety to his constituents, federal fiscal hostility and local white intransigence, limited his options. His reliance on more intensive policing of drugs as a vehicle to stem gang-motivated homicides began a local war on drugs with devastating consequences for black communities